(untitled) (Itinera, 2015)
In Ravaisson’s philosophy, the concept of spontaneity refers to the first, basic and organic form of improvisation. Nature consists in fact of a rational law of development named habit, that regulates all movements, summarizing the external impulsions and the internal penchants in the form of spontaneous activity. However the insertion of spontaneity in nature determines the appearance of unpredictability and negativity in life’s productions, like organic and psychical pathologies. Ravaisson will try to show how this morbid spontaneity belongs to nature’s rationality.